(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study examines the importance and value of Public Relations department (PR) in creating reputation within institutions such as commercial companies. Scholars and PR professionals emphasize that PR has a large impact on creating a two-way communication, promoting and maintain good reputation. The main purpose of this theoretical research is that how corporate reputation is seen and to what extent domestic companies in the Kurdistan Region pay attention to it. In this research, PR literature has been reviewed and it is argued that it can be used as a guideline for creating, developing and maintain institutional reputation.